2003
DOI: 10.1002/ange.200390176
|View full text |Cite
|
Sign up to set email alerts
|

Einkristalle des disubstituierten Anthracens 9,10‐(Ph2PS)2C14H8 detektieren selektiv und reversibel Toluol durch Festkörper‐Fluoreszenz‐Emission

Abstract: Nicht durch π‐Stapelung, sondern durch CH⋅⋅⋅π‐Ringzentrum‐Wechselwirkung wird die Fluoreszenz‐Emission hervorgerufen, die erstmals bei einem heteromolekularen Excimer‐Komplex beobachtet wurde. Bei diesem ist Toluol senkrecht zu einem Ph2P(S)‐disubstituierten Anthracen‐Chromophor ausgerichtet, und die selektive Erkennung von Toluol (siehe Bild) ist auf dieser Grundlage möglich; Benzol wird z. B. nicht erkannt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 47 publications
0
11
0
3
Order By: Relevance
“…Much research has focused on the development of new strong solid-emissive fluorophores. For example, the introduction of bulky substituents onto the original fluorophores, [1c, f, 2j, f, 3] and the formation of clathrates [4,5] or salts [1h] with fluorophores are known to be useful methods to solve the problem of fluorescence quenching by aggregation. The correlation between the solid-state fluorescence properties and the molecular packing structures on the basis of the X-ray crystal structures have also been investigated to elucidate the details of fluorescence quenching.…”
Section: Introductionmentioning
confidence: 99%
“…Much research has focused on the development of new strong solid-emissive fluorophores. For example, the introduction of bulky substituents onto the original fluorophores, [1c, f, 2j, f, 3] and the formation of clathrates [4,5] or salts [1h] with fluorophores are known to be useful methods to solve the problem of fluorescence quenching by aggregation. The correlation between the solid-state fluorescence properties and the molecular packing structures on the basis of the X-ray crystal structures have also been investigated to elucidate the details of fluorescence quenching.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable efforts have demonstrated that bulky and rigid molecules, or awkwardly shaped molecules, tend to include guest molecules because they do not pack easily without guests 6. For example, crystals of anthracene derivatives bearing diphenylphosphanyl groups at the 9‐ and 10‐positions include toluene molecules and show on/off fluorescence switching by absorption and desorption of the guest 5a. Inclusion of various guests into fluorescent hosts will afford a multitude of fluorescent colors as if doping strongly affects the colors of jewels, as seen in sapphires and rubies.…”
Section: Structural and Spectral Properties Of The Crystals Comprisinmentioning
confidence: 99%
“…6 For example, Stalke et al. reported that toluene inclusion crystals are suitable for luminescent chemosensing, as their displayed fluorescent intensity is easily changed by the desorption‐adsorption of guest molecules 6b. Hence such inclusion systems appear to be appropriate for the potential tuning of fluorescent properties.…”
Section: Introductionmentioning
confidence: 99%